2015
DOI: 10.1007/s10067-015-2968-0
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between patient global assessment, pain, and fatigue and influence of other clinical disease activity measures in patients with active rheumatoid arthritis

Abstract: The interplay between patient-reported outcome measures in rheumatology is not well clarified. The objective of the study was to examine associations on the group level and concordance on the individual patient level between patient global assessment (PaGl), pain, and fatigue as scored on visual analog scales (VAS) in the daily clinic by patients with active rheumatoid arthritis (RA). Associations with other measures of disease activity were also examined. Traditional disease activity data on 221 RA patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In other studies , pain has been shown to be the best predictor of PGA, regardless of remission state. In the current study, pain was second to fatigue in explaining PGA in near‐remission.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In other studies , pain has been shown to be the best predictor of PGA, regardless of remission state. In the current study, pain was second to fatigue in explaining PGA in near‐remission.…”
Section: Discussionmentioning
confidence: 76%
“…Another point against PGA is its difficult interpretation . Until now, most studies suggested that PGA essentially reflects pain, function, and fatigue , which in turn have shown a variable correlation with inflammatory markers, in studies that did include psychosocial dimensions or perform multivariable analyses. Considerable percentages of PGA remain unexplained (>22%) , and few studies have explored its relationship with the underlying level of disease activity , or with the patient's psychological profile .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies have reported that pain is a crucial and distressing symptom of RA (Jia & Jackson, 2016;Sturgeon et al, 2016). However, most of these studies have failed to show a strong relationship between pain in RA and objective measures of inflammation (Egsmose & Madsen, 2015;Hammer, Michelsen, Provan et al, 2018). In the past few years, more studies have discovered the influence of several pain appraisal variables, including cognitive beliefs, and behavioral and social responses, to explain the impact of RA on HRQoL (Morgan, 2013;Santos, Duarte, Ferreira, Pinto, Geenen & da Silva, 2018;Sturgeon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an inflammatory autoimmune disease characterised by chronic joint inflammation, which leads to pain, stiffness, function loss, and fatigue [1][2][3]. All of the mentioned complaints can be measured with patient-reported outcome measures (PROMs) like the visual analogue scale (VAS), the Likert scale, the verbal rating scale (VRS) and the numerical rating scale (NRS) [4][5][6]. During outpatient visits, PROMs are taking a more central place because they directly apply to the patients' personal perception and can identify key concerns that need to be addressed [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PROMs have become increasingly important in managing RA in daily clinical practice [6,10,15]. Using PROMs offers opportunities to improve understanding of patients' experiences and responses to therapy, which would otherwise be missed [7,8,16].…”
Section: Introductionmentioning
confidence: 99%